Studi Kualitatif Prosedur Pemasangan Transfusi Darah pada Pasien Anemia - Nova Yustisia; Titin Aprilatutini; Helda Desfianty (Fakultas Ilmu Kesehatan, Universitas Muhammadiyah Bengkulu, 2020)
Anemia is a health problem in the whole world. Anemia cannot be ignored. Treatment varies depending on the cause, if anemia is severe treatment is given with a blood transfusion. Blood transfusion is an interdependent action that must be given according to standard operating procedures (SOP). The purpose of this study was to determine the description of the procedure for blood transfusion in anemic patients in Jasmine Room Dr. M. Yunus Bengkulu. This research is a qualitative descriptive study with a case study approach, involving 10 informants / research subjects. Data collection through interviews and observation of transfusion procedures by nurses. Data analysis techniques used include interview transcripts, data reduction, analysis, data interpretation and triangulation, data which is then concluded. The results of the study showed that the preparation phase of 9 informants prepared complete tools and preparation of patients 2 did not identify the client. The stage of transfusion installation 10 procedures to re-identify patients not in accordance with the SOP, 4 did not wash hands, 1 did not wear gloves. Post-transfusion stage 10 procedures not in accordance with the SOP on the item paying attention to reactions / complications of transfusion and observation of vital signs. Conclusion blood transfusion installation procedures have been carried out according to the SOP, but have not been implemented properly and perfectly, supervision is still lacking and support facilities are inadequate. It is recommended that the results of the study become a baseline for hospitals in improving the quality of services by increasing routine structured supervision, conducting technical training procedures for transfusion installation, and completing supporting facilities.Â Keywords: SOP, Blood Transfusion, Anemia